Explaining gender differences in migrant sorting: evidence from Canada-US migration - Escamilla-Guerrero, D; Lepistö, M; Minns, C (University of Oxford, 2025)
This paper uses newly digitized Canada-Vermont border crossing records from the early twentieth century to document substantial differences in how female and male migrants sorted across US desti nation counties by earnings potential. Income maximization largely explains sorting patterns among men. For single women, gender-based labor market constraints were important, with locations offering more work opportunities attracting women with higher earnings capacity. Among married women, destination choices were much less influenced by labor market characteristics. These findings reveal how labor market constraints based on gender and marriage influence the allocation of migrant talent across destinations.